Effects of Rifamycin Derivatives, Alone and in Combination with Amphotericin B, Against Histoplasma capsulatum - Kobayashi, George S. (1974)
Several derivatives of rifamycin SV inhibited ribonucleic acid synthesis and decreased the viability of Histoplasma capsulatum. Both of these effects were enhanced by low concentrations of amphotericin B. The relative potency of the different rifamycin derivatives against H. capsulatum, when used in combination with amphotericin B or alone, was the same as that reported for the inhibition of the reverse transcriptase of ribonucleic acid tumor viruses.